Manetti C. Letter from the Former Editor-in-Chief - Manetti, Cesare (Annali di Botanica, 2024)
Dear Colleagues, Passionate researchers. in my, albeit brief, experience as Editor-in-Chief of the journal Annali di Botanica I wanted to make an active contribution to its development by trying to bring to light important elements that have characterized the journal from the beginning. It should not surprise you that I am a physical chemist, because several characteristics of Annali di Botanica can be traced back to the systemic vision that characterizes this discipline, which make it a reference not only for the study of ecosystems, but also for issues relating to solutions “nature based”, widely cited in terms of conservation, planning and restoration of territories in a sustainable way as also underline by the strategies to reach different Sustainable Goals of the UN Agenda 2030. Thus, together with the Editorial Committee, I wanted to give, already with the 2023 issue and now with this one which collects the 2024 articles, a multi-dimensional vision of this reality already “distilled” by the subtitle of the magazine “Coenology and plant ecology”: defining “ new trajectories” with respect to which to collect contributions from the various authors